Demographic and Clinicohistological Profiles of Women Diagnosed with Breast Cancer at Al-El Wiya Maternity Teaching Hospital / Baghdad: A Retrospective Study - Zaynab S. Abdulghany1*, Najim Al-Kalidy2 , Maeda H. Mohammad1 , Noor H. Ismail1 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Knowing the incidence of, breast cancer, diagnosis, and treatment methods given a strategic approach forcommunity awareness and rapid management. This study was aimed to: Estimate the demographic patternincluding age, marital status, number of children, mass location, lactation, using contraceptive and smokinghabit and to estimate the pattern of BC risk factors including family history, histological type, grading, andstaging. The retrospective cross-sectional descriptive design was utilized. A total of 282 confirmed breastcancer female patients for the years 2016 to 2018 were included. Overall result showed that the age ofBreast cancer female patients ranged from (25-80) years with a mean (49.12±0.67). Most Breast Cancercases were diagnosed with infiltrating ductal carcinoma (73.4%). The percentage of the discovered tumorwas dominating the right side of the breast (52.8%). Also, 11% of BC females were diagnosed with stageIIa. And 31.2 % of BC cases were diagnosed as grade II. However, 20.2% of the cases were having a familyhistory with breast cancer. Most of the cases (94.7%) were did not checked for biomarker testing, just 12cases (4.3%) were positive ER. And 3.9% of cases tested for PR only 11 cases were positive. While negativeresults for HER2/neu was only in 9 cases (3.2%). Current study validates scientific knowledge about BC inBaghdad. Each year, the incidence rates increase especially for age above 49.